Inhibition of di(2-ethylhexyl) phthalate (DEHP)-induced endocrine disruption by co-treatment of vitamins C and E and their mechanism of action. Issue 16 (18th August 2018) - Choi, Seul Min; Lim, Duck Soo; Kim, Min Kook; Yoon, Sungpil; Kacew, Sam; Kim, Hyung Sik; Lee, Byung-Mu
ABSTRACT: The endocrine disrupting actions of di(2-ethylhexyl) phthalate (DEHP) on testicular functions are postulated to involve excess free radical generation. Thus the aim of this study was to examine the ability of antioxidant vitamins C and E to prevent DEHP-induced testicular disruption in male Sprague-Dawley (SD) rats. SD male rats were administered DEHP alone or DEHP with vitamin C and/or vitamin E for 30 days. DEHP alone increased the levels of testosterone (T) and reduced estradiol (E2 ) concentrations. Supplementation with antioxidant vitamins diminished or restored serum T levels noted in DEHP-treated rats to control values. In contrast vitamins C and E increased E2 levels to control in rats administered DEHP. Antioxidants significantly improved the decreased testicular levels of reduced glutathione and activity of superoxide dismutase compared to DEHP-treatment alone. Co-treatment of vitamins C and E also markedly improved the reduced epididymal sperm head counts and elevated levels of malondialdehyde (MDA) or 8-hydroxydeoxyguanosine (8-OHdG) induced by DEHP treatment. These results support the concept that the adverse actions of DEHP may be related to increased free radical generation while co-treatment with vitamins C and E significantly blocked the actions of DEHP on male testicular functions.